Chloro-hydroxyl-merocyanine based turn-on fluorescent probes for the detection of hydrazine in water and living cells. (April 2022) - Li, Kai-Bin; Chen, Yiyu; Zhou, Tianshuo; Wang, Tianlin; Wu, Dian; Pan, Yuanjiang; Zhang, Siqi; Shi, Wei; Wang, Feiyi; Ren, Jun
Abstract: Hydrazine (N2 H4 ) is a very important chemical reagent which has been widely used in the fields of chemistry industry, aerospace, pesticide production and others. However, N2 H4 is highly toxic and prone to induce a variety of diseases. Hence, we designed two fluorescent probes (CH–NO1, CH–NO2 ) based on chloro-hydroxyl-merocyanine (CHMC) with similar recognition groups. The two probes were synthesized by a simple reaction coupling between CHMC dye and two alkyl bromine compounds. Both probes showed specific off-on response to N2 H4 in aqueous solution with nanomolar LOD (28 nM for CH–NO1 and 38 nM for CH–NO2 ), and without interference by a range of amino acids, anions and cations. Moreover, CH–NO1 can be used for both environmental and biological monitoring of N2 H4 . Highlights: Specific off-on switching response to N2 H4 with near infrared luminescence. The probe showed nanomolar LOD for detecting N2 H4 . Allowed to sense N2 H4 in both environmental and biological monitoring.